Hartvig, Gabriella. Laurence Sterne Magyarorszagon 1790-1860. [Laurence Sterne in Hungary 1790-1860.] Budapest: Argumentum, 2000. 198 pp. - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Gabriella Hartvig’s book has a very modest title, revealing little about the fact that the author uses a variety ofcontexts to widen the scope ofher study of Sterne’s early reception in Hungary. Since knowledge about and response to foreign literature during the decades indicated was much entrenched in the country’s semi-colonial situation, international relations and intranational cultural concepts and endeavours, this complex approach is both justifiable and laudable. The chapters of the book register the interplay of a great number of relevant factors and processes, incorporating data, referential Maria Kurdi details, and thoughtful conclusions that emerge from a vast amount of informed research as proven by the extensive notes.